2020
DOI: 10.1101/2020.04.06.028522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic analysis of tissue cells potentially vulnerable to SARS-CoV-2 infection by the protein-proofed single-cell RNA profiling of ACE2, TMPRSS2 and Furin proteases

Abstract: Single-cell RNA profiling of ACE2, the SARS-CoV-2 receptor, had proposed multiple tissue cells as the potential targets of SARS-CoV-2, the novel coronavirus causing the COVID-19 pandemic. However, most were not echoed by the patients' clinical manifestations, largely due to the lack of protein expression information of ACE2 and co-factors. Here, we incorporated the protein information to analyse the expression of ACE2, together with TMPRSS2 and Furin, two proteases assisting SARS-CoV-2 infection, at single cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…In fact, MERS-CoV was largely propagated by camel-to-human transmissions, as the virus was never able to fully adapt to optimal human-to-human transmission (8). expression information at the single cell level to rank the cells based on their susceptibility to the SARS-CoV-2 infection (20). Consistent with the sc RNA seq data, dual inhibition of the host cell cysteine and serine proteases impeded viral entry into the cell (21).…”
Section: Human Coronavirus (Hcov) Phylogenymentioning
confidence: 78%
“…In fact, MERS-CoV was largely propagated by camel-to-human transmissions, as the virus was never able to fully adapt to optimal human-to-human transmission (8). expression information at the single cell level to rank the cells based on their susceptibility to the SARS-CoV-2 infection (20). Consistent with the sc RNA seq data, dual inhibition of the host cell cysteine and serine proteases impeded viral entry into the cell (21).…”
Section: Human Coronavirus (Hcov) Phylogenymentioning
confidence: 78%
“…The co-expression of ACE2 and TMPRSS2 was reported in type 1 pneumocytes [195], alveolar macrophages [9,192], lymphocytes [9], smooth muscle cells and enterocytes in the gastrointestinal tract [9,195], vessel smooth muscle cells [9], cardiomyocytes [9,192], hepatocytes [169], kidney cells [87], proximal tubule cells [114], and neurons [112], all of which are in line with the common clinical symptoms of COVID-19 [15,19,61,151,166,183,191,197]. Single-cell RNA profiling revealed that male gender, advanced age, and smoking habit can increase the co-expression of ACE2 and TMPRESS2 Viral components are recognized by the MyD88 pathway in the endosome, leading to the releases of IL-6 and NFκB from immune cells including macrophages, monocytes, and dendrites.…”
Section: The Mechanisms Underlying Sars-cov-2 Infectionmentioning
confidence: 98%
“…We also analyzed the overlap of the ACE2+ signatures with SARS-CoV-2-implicated genes and ACE2 signature genes from multiple publicly available, independent studies and found significant shared components across SARS-CoV-2 datasets (Table 2). Specifically, genes associated with ACE2+ expression in DKD were also significantly enriched among host proteins identified to interact with SARS-CoV-2 proteins 33 , host genes upregulated in SARS-CoV-2infected cells 30,32 , and host proteins previously reported to interact with multiple coronaviruses 17 (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Dkd (Supplementarymentioning
confidence: 99%
“…Studies of severe acute respiratory syndrome (SARS) in the early 2000s identified angiotensin-converting enzyme 2 (ACE2) as the primary cell-entry receptor for the SARS coronavirus (SARS-CoV) in humans 14,15 . Recent studies from the pandemic demonstrate that ACE2 is also the primary cell-entry receptor for SARS-CoV-2 13,16,17 and, similar to SARS-CoV, higher ACE2 expression may lead to higher risk of SARS-CoV-2 infection 8,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation